DIAGNOSTIC ASPECTS OF PAGET’S DISEASE OF BONE IN CLINICAL PRACTICE - I. B. Bashkova; N. S. Nikolaev; N. V. Bezlyudnaya; V. A. Kichigin (Научно-практическая ревматология, 2018)
Paget’s disease of bone (PDB) is a chronic localized skeletal disease that belongs to a group of metabolic osteopathies and is characterized by impaired bone remodeling to form foci of increased bone resorption followed by replacement with an excessive amount of defective, less durable bone that is prone to deformities and pathologic fractures. The course of PDB shows three stages: rarefaction, compaction, and coarse-trabecular remodeling – each of which is characterized by certain clinical, biochemical, and radiological manifestations. The majority of the clinical manifestations of the disease are associated with skeletal injury. The disease is characterized by the appearance of bone and joint pain in case of secondary osteoarthritis, bone deformities, pathological fractures, hearing loss due to damage to the skull bones, etc. In many patients, the disease is asymptomatic and detected incidentally after finding a high serum alkaline phosphatase activity or during bone X-ray for any pathological processes, but it can be diagnosed fairly late in the development of complications, as shown in the clinical examples. A combination of clinical, biochemical, morphological data and radiological findings allows for a diagnosis. The use of bisphosphonates is the method of choice for the treatment of PDB.